The Stratigraphy of the New Tuli Basin Fossil Sites in Zimbabwe - Zondo, Michel (University of the Witwatersrand, Johannesburg, 2024)
This thesis investigated new fossil-bearing outcrops of the Mpandi Formation of Zimbabwe, exposed at Sentinel Ranch in the Tuli Basin, at sites named “Wedding Hill “and “Pimwe Hill”. The Mpandi Formation exposures at Sentinel Ranch reveal strata that were deposited in fluvial environments that occasionally experienced flooding in otherwise usually dry and hot climatic conditions. These fluvial systems deposited facies that are mostly dominated by fine sediments and their facies have similarities with those found in the main Karoo Basin of South Africa. The use of borehole data helped establish the thickness of the Mpandi Formation and the explorable portion of the formation was estimated to be around 54 metres. Detrital zircons collected from main Sentinel outcrops were used to estimate the maximum depositional age of the sediments using inductively coupled plasma mass spectrometer (LA-ICPMS) methods. Although sparse, the youngest zircons in these samples yielded ages of 199.2 ± 5.1 Ma and 200.8 ± 5.8 Ma, with error bars suggesting maximum depositional ages in the earliest Jurassic or possibly the latest Triassic. A bonebed at the Wedding Hill site produced many postcranial bones of sauropodomorphs, including the articulated leg of a very large individual sauropodomorph, and the first theropod bones recorded from the Mpandi Formation at Sentinel. The discoveries improve our knowledge of the fauna diversity of the Mpandi Formation, permitting more accurate biostratigraphic correlation and enhancing our understanding of the Triassic- Jurassic interval.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2024.
Keywords: Stratigraphy; Tuli Basin; Fossil sites; UCTD; SDG-15: Life on land; SDG-4: Quality education